Hydroxyapatite in Oral Biofilm Management - Meyer, Frederic; Enax, Joachim (European Journal of Dentistry, 2019)
Particulate hydroxyapatite, Ca5 (PO4)3 (OH), shows a good biocompatibility and is used as a biomimetic ingredient in dental care formulations due to its similarity to human enamel. Numerous studies show its efficiency, for example, in reducing dentin hypersensitivity, and in the remineralization of enamel and dentin. In addition, oral care products with hydroxyapatite improve periodontal health under in vivo conditions. This review article summarizes data on the effects of hydroxyapatite particles in oral biofilm management. Two databases (PubMed and SciFinder) were searched for studies using specific search terms. In contrast to frequently used antibacterial agents for biofilm control, such as chlorhexidine, stannous salts, and quaternary ammonium salts, hydroxyapatite particles in oral care products lead to a reduction in bacterial attachment to enamel surfaces in situ without having pronounced antibacterial effects or showing unwanted side effects such as tooth discoloration. Furthermore, antibacterial agents might lead to dysbiosis of the oral ecology, which was recently discussed regarding pros and cons. Remarkably, the antiadherent properties of hydroxyapatite particles are comparable to those of the gold standard in the field of oral care biofilm management, chlorhexidine in situ. Although biomimetic strategies have been less well analyzed compared with commonly used antibacterial agents in oral biofilm control, hydroxyapatite particles are a promising biomimetic alternative or supplement for oral biofilm management.
Keywords: biofilm; caries; hydroxyapatite; periodontitis